Oil Windfalls in Ghana : A DSGE Approach - Dagher, Jihad (IMF Working Papers; Working Paper ;, 2010)
We use a calibrated multi-sector DSGE model to analyze the likely impact of oil windfalls on the Ghanaian economy, under alternative fiscal and monetary policy responses. We distinguish between the short-run impact, associated with demand-related pressures, and the medium run impact on competitiveness and growth. The impact on inflation and the real exchange rate could be moderate, especially if the fiscal authorities smooth oil-related spending or increase public spending's import content. However, a policy mix that results in both a fiscal expansion and the simultaneous accumulation of the foreign currency proceeds from oil as international reserves-to offset the real appreciation-would raise demand pressures and crowd-out the private sector. In the medium term, the negative impact on competitiveness-resulting from 'Dutch Disease' effects-could be small, provided public spending increases the stock of productive public capital. These findings highlight the role of different policy responses, and their interaction, for the macroeconomic impact of oil proceeds.